Efecto de la regulación bancaria sobre el crecimiento económico: costos y política macro-prudencial de largo plazo (2021)
The effect of 2008 financial crisis was magnified by the lax banking regulation. By that date the measures that ruled the banking sector was the Basel II Agreements, which established the solvency minimums that were apparently high enough for the date. However, after the Lehman bankruptcy and the contagion effect over the rest of banks, the fragility of the banking regulation was evident. After a new assessment of banking regulation measures, the major banking regulacy entities released a new set of recommendations: The Basel III Agreements. These established new solvency minimums higher and with higher liquidity that could make the capital reserves able to afford losses in tension times...